THEORY OF JOB SATISFACTION AND JOB PERFORMANCE: TIME FOR A SECOND LOOK - Hermeindito Kaaro (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2004)
Relationship between job satisfaction and job performance has been extensively searched in previous studies. However, bulk evidences show the correlation between the two is relatively low. This study attempts to refine the concepts of job satisfaction and job performance and proposes mechanism relationship between the two. The present model shows that mechanism between the two is not clearly matching pair. The concepts of job satisfaction more concerns on a set of jobs. The concepts of job performance, on the other hand, more concerns on a particular job. Some methodological problems also arise in empirical research. Both theoretical and methodological problems may lead such previous studies in searching relationship between job performance and job satisfaction has been trapped out of track. Hence, it should not be surprising that such empirical findings are relatively weak to improve this relationship. Some implications for further studies are discussed in this paper.